The ciliopathy protein TALPID3/KIAA0586 acts upstream of Rab8 activation in zebrafish photoreceptor outer segment formation and maintenance - Ojeda Naharros, Irene; Cristian, Flavia-Bianca (Scientific reports, 2018)
Ciliopathies are human disorders caused by dysfunction of primary cilia, ubiquitous microtubule-based organelles involved in signal transduction. Cilia are anchored inside the cell through basal bodies (BBs), modified centrioles also acting as microtubule-organization centers. Photoreceptors (PRs) are sensory neurons, whose primary cilium forms a highly specialized compartment called the outer segment (OS) responsible for sensing incoming light. Thus, ciliopathies often present with retinal degeneration. Mutations in KIAA0586/TALPID3 (TA3) cause Joubert syndrome, in which 30% of affected individuals develop retinal involvement. To elucidate the function of TALPID3 in PRs, we studied talpid3 zebrafish mutants and identified a progressive retinal degeneration phenotype. The majority of PRs lack OS development due to defects in BB positioning and docking at the apical cell surface. Intracellular accumulation of the photopigment opsin leads to PR cell death of moderate severity. Electroretinograms demonstrate severe visual impairement. A small subset of PRs display normally docked BBs and extended OSs through rescue by maternally-deposited Talpid3. While localization of the small GTPase Rab8a, which plays an important role in BB docking, appears unaffected in talpid3−/− PRs, overexpression of constitutively active Rab8a rescues OS formation, indicating that the role of Ta3 in early ciliogenesis lies upstream of Rab8a activation in PRs.
Gesehen am 09.12.2019